PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE) DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR HEALTHCARE PAPAN UTAMA DI BURSA EFEK INDONESIA PERIODE 2016-2022 - M. Zainuddin; Novia Nour Halisa; Noor Hidayati; Nurul Wahyuni (Smart Business Journal (SBJ), 2024)
The study aimed to investigate the individual as well as combined effects of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) on the stock prices of primary healthcare companies listed on the Indonesia Stock Exchange from 2016 to 2022. A quantitative approach using an explanatory research design was employed for this study. The research analyzed the financial statements of prominent healthcare companies listed on the Indonesia Stock Exchange as its population. The sample consisted of financial reports from the years 2016 to 2022, selected through purposive sampling. The dataset included secondary data sourced from financial reports provided by the IDX, gathered through documentation and literature review. The data analysis involved multiple regression analysis conducted using SPSS version 26.0 software. The results suggest that there could be times when Return on Assets (ROA) significantly affects stock prices, but this impact may not be constant. Conversely, the influence of Return on Equity (ROE) on stock prices might not always be significant. Similarly, Net Profit Margin (NPM) may not consistently affect stock prices in certain situations. However, when taken together, Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) collectively demonstrate a notable influence on stock prices.